2001
DOI: 10.1134/1.1385420
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear standing waves in a layer excited by the periodic motion of its boundary

Abstract: -A new analytical approach is developed for the description of standing waves caused by arbitrary periodic vibration of a boundary. The approach is based on the nonlinear evolution equation written for an auxiliary function. This equation offers the possibility to study not only the steady-state acoustic field, but also its evolution in time. One can take into account the dissipative properties of the medium and the difference between one of the resonant frequencies and the fundamental frequency of the driving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…A detailed explanation and the physical foundation of this approach can be found in [2,12]. A similar approach can be used for standing waves in a cubically nonlinear resonator.…”
Section: Methods For Simplifying the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed explanation and the physical foundation of this approach can be found in [2,12]. A similar approach can be used for standing waves in a cubically nonlinear resonator.…”
Section: Methods For Simplifying the Problemmentioning
confidence: 99%
“…Such a nonlinearity is known to be dominant for acoustic waves in fluids and for longitudinal waves in solids. Reviews of the results obtained for quadratically nonlinear resonators can be found in [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…This approach is described in detail in [1] and used by several authors before. For quadratic nonlinearity and harmonic vibration of one wall the functional equation is derived [1]:…”
Section: Methods For Analytical Solutionmentioning
confidence: 99%
“…Parameter D is the small ratio of the length of resonator to the characteristic absorption distance. The absorption coefficient b and corresponding dissipative terms are not presented, for simplicity, in the initial functional equation (1), but this modifying can be easily performed in the differential equation (2). Exact analytical solutions to equation (2) for travelling waves were obtained in Refs.…”
Section: Methods For Analytical Solutionmentioning
confidence: 99%
See 1 more Smart Citation